The Transcription Factor ThPOK Regulates ILC3 Lineage Homeostasis and Function During Intestinal Infection - Gao, Xianzhi; Shen, Xin; Liu, Kuai; Lu, Chenyu; Fan, Ying; Xu, Qianying; Meng, Xiaoyu; Hong, Shenghui; Huang, Zhengwei; Liu, Xia; Lu, Linrong; Wang, Lie (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) have been identified as a heterogeneous population of lymphocytes that mirrors the cytokine and transcriptional profile of adaptive T cells. The dynamic balance between key transcription factors determines the heterogeneity, plasticity, and functions of ILC subsets. The transcription factor ThPOK is highly conserved in biological evolution and exerts pivotal functions in the differentiation of T cells. However, the function of ThPOK in ILC3s has not been identified. Here, we found that ThPOK regulated the homeostasis of ILC3s, as mice lacking ThPOK showed decreased NKp46+ ILC3s and increased CCR6- NKp46- ILC3s. ThPOK-deficient mice were more sensitive to S. typhimurium infection due to the impaired IFN-γ secretion of NKp46+ ILC3s. Furthermore, ThPOK participates in ILC3-mediated control of C. rodentium infection by negatively regulating IL-17A secretion. ThPOK preserves the identity of NKp46+ ILC3s by repressing RORγt, which indirectly releases T-bet expression. On the molecular level, ThPOK directly binds to Rorc and Il23r to restrain their expression which further modulates IL-17A secretion. Collectively, our analysis revealed a critical role of ThPOK in the homeostasis and functions of ILC3 subsets.